The Probability of Two Female Main Characters to Become Radical Subject in “The Other Boleyn Girl” Novelby Philippa Gregory - Zietha Arlamanda Asri (Universitas Brawijaya, 2021)
Individual actions will usually be motivated by a symbolic structure in accordance with the society in where the subject lives. This makes certain individuals and their behavior never be liberated from the symbolic order appliedin their society. In other words, these individuals can never be authentic because all actions must be under the control of appropriate laws and regulations. This certainly controls the pattern of life sincethe individual’s mindset is subject to the ideology that hegemonies them. In the Zizekian perspective, the subject is always in a lacking condition in their symbolic order, so that they continue to desire the Real. When their desire for the Real is fulfilled through concrete actions that go beyond symbolic laws, authentic subjectivity is formed.This studyanalyzed two main problems: (1) the actions or behavior of the main female characters (Anne and Mary) which were assumed to be radical behavior, and (2) a comparison of the chances to become a radical subject in “The Other Boleyn Girl” novel by using the concept of a radical subject proposed by Zizek.